2004
DOI: 10.1182/blood-2003-08-2688
|View full text |Cite
|
Sign up to set email alerts
|

pDP4, a novel glycoprotein secreted by mature granulocytes, is regulated by transcription factor PU.1

Abstract: The transcription factor PU.1 (Spi-1) is a well-characterized regulator of myeloid and lymphoid development. However, its role in mature functional cells is poorly studied. Here we report the characterization of the novel murine gene pDP4 (PU.1 difference product 4), which is absent from fetal livers of PU.1-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…RT-PCR and quantitative RT-PCR to amplify OLFM4 were performed as previously described (8,36). The primers and probes for cytokines and chemokines were all purchased from Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-PCR and quantitative RT-PCR to amplify OLFM4 were performed as previously described (8,36). The primers and probes for cytokines and chemokines were all purchased from Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%
“…However, genetic knock-out mice for myocilin (6) and pancortin-2 (7) demonstrate no obvious phenotypes. OLFM4 is constitutively expressed in neutrophils and the gastrointestinal tract epithelial cells (2,8). A recent study showed that OLFM4 is a target gene of Notch pathway (9), suggesting a potential role for OLFM4 for Notch mediated cell differentiation, proliferation, and immune response to inflammation.…”
Section: Nf-κb | Nucleotide Oligomerization Domain-1 and -2mentioning
confidence: 99%
“…15 Interestingly, mice are hypomorphic for PU.1, but neither PU.1 þ /À nor PU.1 À/À mice develop AML, suggesting that some remaining activity of Pu.1 is required probably to initiate lineage commitment. 19 The most common translocation in APL fuses the RARA on chromosome 17 to the PML gene on chromosome 15, leading to a PML/RARA fusion protein (accounting for 495% of cases). In the remaining cases of APL, the RARA gene is fused to other genes like PLZF, NPM, NuMA and STAT5, arguing for a common molecular mechanism involving the disruption of the RARA pathway.…”
Section: Tumor Suppressor or Proto-oncogene?mentioning
confidence: 99%
“…In the rat eye, the Hnoel-iso gene was more actively expressed in the iris and sclera than in other eye structures (18). The human GW122/ hGC-1 gene, which is also named pDP4 in mice (19) and tiarin in Xenopus (7), is expressed in bone marrow, small intestine, colon, and prostate (20). The myocilin gene is highly expressed in the eye trabecular meshwork and sclera and less actively expressed in several other ocular and non-ocular tissues (1,(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…It has been suggested that the upstream regulatory factor may be essential for the regulation of the MYOCILIN gene (37). The ETSfamily transcription factor PU.1 (Spi-1) may be involved in the regulation of the pDP4 gene in mature mouse granulocytes (19).…”
mentioning
confidence: 99%